Long-Lasting Rituximab-Induced Reduction of Specific—But Not Total—IgG4 in MuSK-Positive Myasthenia Gravis - Marino, Mariapaola; Basile, Umberto; Spagni, Gregorio; Napodano, Cecilia; Iorio, Raffaele; Gulli, Francesca; Todi, Laura; Provenzano, Carlo; Bartoccioni, Emanuela; Evoli, Amelia (Frontiers in Immunology, 2020)
Rituximab (RTX), an anti-CD20 monoclonal antibody (Ab) has increasingly been used in refractory myasthenia gravis (MG) with a better response in patients with Abs to the muscle-specific tyrosine kinase receptor (MuSK) than in other MG subgroups. Anti-MuSK Abs are mostly IgG4 with a proved pathogenic effect and a positive correlation with clinical severity. The rapid and sustained response to RTX may be related to MuSK Abs production by short-lived plasma cells derived from specific CD20+ B cells. Here, we investigated the long-term effects of RTX in nine refractory MuSK-MG patients with a follow-up ranging 17 months-13 years. We titrated patients’ sera for MuSK specific IgG and IgG4, along with total IgG and IgG4 serum levels. Optimal response to RTX was defined as achievement and maintenance of minimal manifestations (MM)-or-better status, together with a ≥50% steroid reduction, withdrawal of immunosuppressants and no need for plasma-exchange. After a first course of RTX, eight patients improved, with optimal response in six and partial in two who did not achieve MM-or-better status; a single patient showed no response. At baseline, MuSK-IgG and -IgG4 serum titers were positive in all patients, ranging from 2.15 to 49.5 nmol/L and from 0.33 to 46.2 nmol/L, respectively. MuSK Abs mostly consisted of IgG4 (range 63.80-98.86%). RTX induced a marked MuSK Ab reduction at 2-7 months and at 12-24 months (p<0.02 for MuSK-IgG and p<0.01 for MuSK-IgG4). In patients with longer follow-up, MuSK Ab titers remained suppressed paralleling clinical response. In a patient who achieved complete remission, MuSK Abs became negative after 11 years since RTX, while specific IgG4 were no more detectable within two years. In the patient who did not respond, MuSK IgG and IgG4 remained unchanged. In this series, both total IgG and IgG4 were only transiently reduced (p< 0.05) at 2-7 months. The different reduction timing between specific and total IgG4 supports the view that short-lived plasma cells are the MuSK Abs main producers. The ratio between short- and long-lived specific plasma cells may influence the response to RTX, and the B cell severe depletion may silence the self-maintaining autoimmune reactivity.